Provoking local ethnic violence – A global study on ethnic polarization and terrorist targeting. (May 2017) - Python, Andre; Brandsch, Jürgen; Tskhay, Aliya
Abstract: This article theorizes and empirically investigates the link between ethnic divisions and terrorist attacks on a local scale. We argue that terrorists in ethnic contexts can use two separate provocation strategies: one targeting the government and one targeting opposing ethnic groups in order to stir up ethnic conflict. Following the second strategy, terrorists should target especially highly polarized localities, which are more prone to an escalation of ethnic conflict. Empirically, we suggest an innovative approach to estimate ethnic division indices at sub-national level, using 55 × 55 km grid cells as the unit of observation. Our empirical analysis uses negative binomial regression models including a spatially lagged dependent variable to account for spatial autocorrelation. The analysis reveals that, from 2002 to 2014, areas with high levels of ethnic polarization encountered more terrorist attacks. The results are robust for different model specifications and ethnic polarization remains the most robust ethnic predictor. We conclude that the pattern of terrorist attacks is consistent with our argument that terrorism can be used as a strategy for local ethnic provocation.